Design and synthesis of chromone-nitrogen mustard derivatives and evaluation of anti-breast cancer activity - Jianan Sun; Jiahui Mu; Shenglin Wang; Cai Jia; Dahong Li; Huiming Hua; Hao Cao (Taylor & Francis Group, 2022)
Chromone has emerged as one of the most important synthetic scaffolds for antitumor activity, which promotes the development of candidate drugs with better activity. In this study, a series of nitrogen mustard derivatives of chromone were designed and synthesised, in order to discover promising anti-breast tumour candidates. Almost all target derivatives showed antiproliferative activity against MCF-7 and MDA-MB-231 cell lines. In particular, methyl (S)-3-(4-(bis(2-chloroethyl)amino)phenyl)-2-(5-(((6-methoxy-4-oxo-4H-chromen-3-yl)methyl)amino)-5-oxopentanamido)propanoate showed the most potent antiproliferative activity with IC50 values of 1.83 and 1.90 μM, respectively, and it also exhibited certain selectivity between tumour cells and normal cells. Further mechanism exploration against MDA-MB-231 cells showed that it possibly induced G2/M phase arrest and apoptosis by generating intracellular ROS and activating DNA damage. In addition, it also inhibited MDA-MB-231 cells metastasis, invasion and adhesion. Overall, methyl (S)-3-(4-(bis(2-chloroethyl)amino)phenyl)-2-(5-(((6-methoxy-4-oxo-4H-chromen-3-yl)methyl)amino)-5-oxopentanamido)propanoate showed potent antitumor activities and relatively low side effects, and deserved further investigation.